Broadly effective metabolic and immune recovery with C5 inhibition in CHAPLE disease - ÖZEN, AHMET OĞUZHAN; ERTEM ŞAHİNOĞLU, DENİZ; AYDINER, ELİF; TUTAR, ENGİN; ERGELEN, RABİA; BARIŞ, SAFA (NATURE RESEARCH, 2021)
CHAPLE disease is a lethal syndrome caused by genetic loss of the complement regulatory protein CD55. Lenardo, Ozen and their colleagues report that blockade of C5 complement activation in a small cohort of pediatric patients with CHAPLE disease reduced gastrointestinal pathology and restored their immunity and growth. Complement hyperactivation, angiopathic thrombosis and protein-losing enteropathy (CHAPLE disease) is a lethal disease caused by genetic loss of the complement regulatory protein CD55, leading to overactivation of complement and innate immunity together with immunodeficiency due to immunoglobulin wasting in the intestine. We report in vivo human data accumulated using the complement C5 inhibitor eculizumab for the medical treatment of patients with CHAPLE disease. We observed cessation of gastrointestinal pathology together with restoration of normal immunity and metabolism. We found that patients rapidly renormalized immunoglobulin concentrations and other serum proteins as revealed by aptamer profiling, re-established a healthy gut microbiome, discontinued immunoglobulin replacement and other treatments and exhibited catch-up growth. Thus, we show that blockade of C5 by eculizumab effectively re-establishes regulation of the innate immune complement system to substantially reduce the pathophysiological manifestations of CD55 deficiency in humans.
Keywords: DECAY-ACCELERATING FACTOR; PROTEIN-LOSING ENTEROPATHY; HEMOLYTIC-UREMIC SYNDROME; LUPUS-ERYTHEMATOSUS SLE; ENDOTHELIAL-CELLS; CD55 DEFICIENCY; SINGLE-CELL; COPY-NUMBER; COMPLEMENT; ECULIZUMAB